Filter Trust Region Method for Nonlinear Semi-Infinite Programming Problem. (8th July 2018) - Su, Ke; Xu, Chun; Ren, Lele
Abstract : We present a filter trust region method for nonlinear semi-infinite programming. Based on the discretization technique and motivated by the multiobjective programming, we transform the semi-infinite problem into a finite one. Together with the filter technique, we propose a modified method that avoids the merit function. Compared with the existing methods, our method is more flexible and easier to implement. Under some mild conditions, the convergent properties are proved. Moreover, the numerical results are reported in the end.